Harmonisasi Hukum Positif dalam Pengaturan Alat Kelengkapan DPRD: Harmonization of Positive Law in Regulating DPRD Complements - Maskuri, Maskuri; Muhammad Junaidi; Fanesa Amada (Journal Juridisch, 2025)
This study analyzes the regulation of council apparatus in the Regional People's Representative Council of Demak Regency and formulates an ideal model for harmonizing Indonesia’s positive law. The research background concerns the disharmony among several legal instruments, especially the MD3 Law, the Regional Government Law, and Government Regulation Number 12 of 2018, which undermines the effectiveness of the council in carrying out its legislative, oversight, and budgetary functions. The urgency lies in the need for an integrated legal system to prevent conflicting interpretations and overlapping authority. Using a normative juridical method with conceptual and descriptive analytical approaches, this study evaluates statutory documents and the institutional practices of the Demak council. The findings reveal a clear discrepancy between das sollen and das sein characterized by weak inter organ coordination and functional disharmony. The novelty of this study lies in proposing a harmonization model that integrates vertical, horizontal, and functional approaches grounded in the principle of socio equilibrium which aligns legal structure with institutional realities. The study concludes that revising the council’s internal regulations, strengthening institutional capacity, and issuing national guidelines for legal harmonization are essential steps. Key recommendations include preparing an academic manuscript on harmonization, improving institutional training, and encouraging meaningful public participation.   Penelitian ini menganalisis pengaturan mengenai perangkat dewan pada Dewan Perwakilan Rakyat Daerah Kabupaten Demak serta merumuskan model ideal untuk harmonisasi hukum positif Indonesia. Latar belakang penelitian ini berkaitan dengan disharmoni berbagai instrumen hukum, khususnya Undang Undang MD3, Undang Undang Pemerintahan Daerah, dan Peraturan Pemerintah Nomor 12 Tahun 2018 yang melemahkan efektivitas DPRD dalam menjalankan fungsi legislasi, pengawasan, dan penganggaran. Urgensi penelitian terletak pada kebutuhan membangun sistem hukum terpadu guna mencegah perbedaan penafsiran dan tumpang tindih kewenangan. Dengan menggunakan metode yuridis normatif melalui pendekatan konseptual dan deskriptif analitis, penelitian ini mengevaluasi dokumen peraturan perundang-undangan dan praktik kelembagaan DPRD Demak. Temuan penelitian menunjukkan adanya kesenjangan antara das sollen dan das sein yang tercermin dari lemahnya koordinasi antarlembaga dan disharmoni fungsi. Kebaruan penelitian ini terletak pada model harmonisasi yang memadukan pendekatan vertikal, horizontal, dan fungsional berdasarkan prinsip socio equilibrium yang menyelaraskan struktur hukum dengan realitas kelembagaan. Penelitian ini menyimpulkan bahwa revisi peraturan internal DPRD, penguatan kapasitas kelembagaan, dan penerbitan pedoman nasional tentang harmonisasi hukum merupakan langkah penting. Rekomendasi utama mencakup penyusunan naskah akademik harmonisasi, peningkatan pelatihan kelembagaan, dan mendorong partisipasi publik secara substansial.